Effectiveness of virtual reality distraction in pediatric dentistry: Efektivitas virtual realitas distraksi dalam kedokteran gigi anak - Resti Allo Padang; Andi Sri Permatasari (Makassar Dental Journal, 2026)
When treating children, it is very important to prioritise comfort, effectiveness, safety, and conservative treatment methods. A positive dental experience is essential for children as it minimises anxiety in patients and parents. Distraction is one technique for successful treatment. It is necessary for controlling be-haviour and managing pain in children. The use of technology such as virtual reality (VR) has recently become an interesting tool for paediatric dentists, as it shifts children's focus away from fear and pain. Video games and digital games serve as VR content in some studies. The study shows that VR and smart-phone games are the most effective distraction techniques for managing negative behaviour in paediatric dental patients. This review provides an overview of the effectiveness of VR distraction in paediatric dentistry. It is concluded that distraction using VR in paediatric dentistry can reduce anxiety and pain levels during dental treatment.